1975
DOI: 10.1002/bjs.1800621205
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metal clips on the tensile properties of healing skin wounds

Abstract: The effects of nylon sutures and metal skin clips on the tensile properties of healing skin wounds have been studied in the pig. Wounds closed with clips have significantly poorer mechanical properties at 5, 7 and 14 days after wounding than similar wounds in the same animal closed with interrupted nylon sutures. This difference increased progressively with the period of retention of the clips. It is also shown that in equivalent groups of 14-day wounds, those in which clips were retained after the seventh day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The point of rupture of the specimen was noted carefully to ensure this conformed to the site of the wound. The complexity of wound biomechanics means that description based on only one parameter may be misleading 18 . Quantitative properties can be calculated from the load versus extension curve (Fig.…”
Section: Determination Of Wound Biomechanics By Tensiometrymentioning
confidence: 99%
“…The point of rupture of the specimen was noted carefully to ensure this conformed to the site of the wound. The complexity of wound biomechanics means that description based on only one parameter may be misleading 18 . Quantitative properties can be calculated from the load versus extension curve (Fig.…”
Section: Determination Of Wound Biomechanics By Tensiometrymentioning
confidence: 99%
“…It also is interesting that incision breaking strengths were less on day seven than on day three for all groups. This may be explained in terms of the complexity of wound biomechanics [24,25]. Early healing is characterized by the deposition of a ''fibrin glue,'' the elastic component of which would result in a greater force being required per unit extension for incisions analyzed at an earlier time.…”
Section: Discussionmentioning
confidence: 99%
“…26 Studies in animals have suggested, however, that wound tensile strength is actually greater for staples compared with sutures. Despite the remarkable amount of time saved by placing staples instead of sutures, early an imal and clinical investigations included questions about the capacity of staples to appose wound edges as accurately or to promote wound tensile strength as effectively as sutures.…”
Section: Wound Staplingmentioning
confidence: 99%